2013
DOI: 10.1038/pr.2013.142
|View full text |Cite
|
Sign up to set email alerts
|

Cysteinyl leukotriene levels correlate with 8-isoprostane levels in exhaled breath condensates of atopic and healthy children

Abstract: Background: Cysteinyl leukotrienes are important mediators of airway inflammation, whereas 8-isoprostane is a biomarker of oxidative stress. This study evaluated the distributions of cysteinyl leukotriene and 8-isoprostane concentrations in exhaled breath condensates (EBCs) of children. The relationship between cysteinyl leukotriene and 8-isoprostane concentrations in the EBCs was also evaluated. Methods: The EBCs were collected from 34 children with allergic respiratory diseases and 24 healthy children. All r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Among them, many studies indicated 8-isoPGF 2α as reliable indicator of lipid peroxidation because of its stability. Additionally, elevated levels of 8-isoPGF 2α have been noted in association with exposure to toxic compounds and may thus indicate disease progression in the lungs and kidneys [ 27 33 ]. Moreover, HNE-MA, a biomarker detected in rats after an acute oxidative stress insult, can indicate levels of lipid peroxidation and be used to evaluate cytotoxicity in biological systems [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, many studies indicated 8-isoPGF 2α as reliable indicator of lipid peroxidation because of its stability. Additionally, elevated levels of 8-isoPGF 2α have been noted in association with exposure to toxic compounds and may thus indicate disease progression in the lungs and kidneys [ 27 33 ]. Moreover, HNE-MA, a biomarker detected in rats after an acute oxidative stress insult, can indicate levels of lipid peroxidation and be used to evaluate cytotoxicity in biological systems [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Through a targeted approach, many single mediators related to inflammation and oxidative stress have been searched in EBC. Among them, the most relevant are:pH, which tended to be lower in children with severe or acute asthma but not in mild and stable disease [101,102,103];Leukotrienes (LT): LTB4, a potent inflammatory mediator and a chemoattractant for neutrophils, was increased in the EBC of asthmatic children, being twice as high in steroid-naïve patients with asthma as in healthy subjects [104,105]; Cysteinyl leukotrienes (LTC4, LTD4, and LTE4), powerful constrictors and proinflammatory mediators, were increased in particular in unstable or severe asthma [106,107,108];8-isoprostane, hydrogen peroxide (H 2 O 2 ), and other markers of oxidative stress, which were increased in asthma [107,109]; in particular, H 2 O 2 correlated with disease severity, disease control, and response to steroid treatment [110,111];3-nitrotyrosine (3-NT) and other nitric oxide metabolites that were more concentrated in the EBC of asthmatic children than in healthy controls [102,112,113]. …”
Section: Asthmamentioning
confidence: 99%
“…Cys‐LT EBC levels are correlated with the severity of asthma (Kazani et al , ). Cys‐LT levels in exhaled breath condensate were found to be elevated in children with asthma and allergic rhinitis (Wan et al , ). Levels of 8‐iso‐PGE 2 in exhaled breath condensate were found to be elevated in aspirin‐hypersensitive asthmatics (Mastalerz et al , ).…”
Section: Lipid Mediators In Body Fluidsmentioning
confidence: 99%